Editorial Advisory Board Members on Reimagining Higher Education Internationalization and Internationalization of the Curriculum. (September 2021) - Whitsed, Craig; Burgess, Madeline; Ledger, Susan
This research explores how editorial advisory board members across four highly ranked international higher education–focused journals understand higher education internationalization generally, and internationalization of the curriculum (IoC) specifically. Notionally, as gatekeepers, editorial advisory board members hold a powerful strategic position in the scholarly debates that characterize an active discipline, and can indirectly assert a strong influence over the academic direction of the field(s) to which they belong. All editorial advisory members for the journals Higher Education, Studies in Higher Education, Higher Education Research & Development, and the Journal of Studies in International Education were invited to contribute to this research with 25 ( N = 25, 30%) consenting to participate. Utilizing qualitative, semi-structured interviewing, participants discussed their views on higher education internationalization, IoC, and the importance of these in the contemporary university. Participants also discussed what dimensions of IoC need to be further addressed in higher education discourses and research, and opportunities and challenges they foresee concerning higher education internationalization now and into the future. Findings reveal, for participants, internationalization continues to be perceived as a multivocal, largely Anglo-European, and neoliberal enterprise which is at a crossroad, and needs to be reimagined for the betterment of all in society. Collectively, participants draw attention to a lack of criticality and problematization within higher education internationalization discourses, and highlighted the need for research, scholarship, and academic leaders to expand the focus of IoC to address future global challenges and needs.